Direito à educação e o Ministério Público do Pará - sua atuação como agente fiscalizador - BRAGA, Diana Barbosa Gomes (Universidade Federal do Pará, 2012)
This dissertation aims to demonstrate the role of prosecutors and his role as supervising agent of the state in ensuring the human right to education. The same is bound to the Post Graduate Institute of Education UFPA line Public Policy Education. We seek to understand how the movement to expand the state in ensuring social rights permeated by the participation of civil society. This study examines the work of the institution through the action of the Courts of Law for Children and Youth and Attorney Constitutional Education in the city of Bethlehem from 2002 to 2008. With reference to the legal-political paradigm of the 1988 Federal Constitution, which assigns this state entity, the promotion of social interests as well as the supervision and control among the population of the legality of the interests and public policies related to educational services, we seek to understand the limits and possibilities that this body has. Education, public right, is highlighted in our last Charter, ensuring political force in the legal area. The possibilities of putting it was extended, because its security is supported in normative constitutional and infra, and consolidated through the implementation of public educational policies. In defense of law, the democratic regime, the social interests of this institution presents itself differently from other state bodies, as to protect the rights of collective and can claim responsibility and through its legal instruments to statehood. This study is structured in three parts. We begin the discussion of the state attempting to establish relations of civil society participation in the conquest of rights, we support the political theorists and Antonio Gramsci elect to have better understood that the right is not something mechanical that it provides for applicability of the law, but this is a human product coming from the conflicts of interest between civil society and the state. Then we draw outlines a brief history of the institution and its relationship with the right to education actually Pará, contextualized with official figures showing the educational scenario in the region. Finally we analyze the procedures used by the entity seeking to ensure the right to education, with its limits and its progress in combating educational inequalities. The methodological procedures to understand the principle of this study was chosen case study, together with collection of different sources which are literature, documents and field work through semi-structured interviews, which enable to answer the purpose stated.